2012
DOI: 10.1155/2012/457054
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Damage and Apoptosis in Exfoliated Buccal Cells from Individuals with Oral Cancer

Abstract: This study aimed to investigate cytological abnormalities indicative of chromosome damage (micronuclei) and apoptosis (karyorrhexis, pyknosis, and condensed chromatin) in exfoliated cells from the buccal mucosa of patients with oral cancer and control subjects. The sample included twenty individuals with oral cancer and forty individuals with normal buccal mucosa. Material was collected from the cheek epithelium in areas with lesions and areas without abnormalities. A minimum of one thousand cells was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…These observations indicate genetic damage [32], which correlates with cancer of the oral cavity [33]. Our findings were in accordance with several recent case-control studies; they revealed that spontaneous genetic damage in exfoliated buccal cell MN frequencies of patients was significantly higher than that of controls and thus genetic instability appeared to exist in exfoliated buccal cell MN frequencies of HNC patients [3438]. Another study of HNC patients undergoing radiotherapy observed increased genomic instability in somatic cells (exfoliated buccal epithelia) in comparison to healthy control subjects [3941].…”
Section: Discussionsupporting
confidence: 90%
“…These observations indicate genetic damage [32], which correlates with cancer of the oral cavity [33]. Our findings were in accordance with several recent case-control studies; they revealed that spontaneous genetic damage in exfoliated buccal cell MN frequencies of patients was significantly higher than that of controls and thus genetic instability appeared to exist in exfoliated buccal cell MN frequencies of HNC patients [3438]. Another study of HNC patients undergoing radiotherapy observed increased genomic instability in somatic cells (exfoliated buccal epithelia) in comparison to healthy control subjects [3941].…”
Section: Discussionsupporting
confidence: 90%
“…We included laryngeal subjects in this analysis because alcohol has been shown to be a significant risk factor for laryngeal cancer even though drinking does not normally expose the larynx to alcohol. Evidence from case-control studies indicates that alcohol consumption is a significant risk factor for laryngeal cancer [18,31]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential for metastasis, cancer is characterized by the loss of the ability of cells to evolve to death when genetic damage occurs (apoptosis). 17,18 Therefore, MNCs are identified as a potential biomarker and a sensitive onco-indicator in Cytogenetics and micronucleus test (MNT) has been accepted as an ideal in vivo cytogenetic screening procedure for the detection of induced structural chromosome aberrations in general and early detection of oral cancer, in particular. 19 The MNT, developed by Heddle 20 & Schmid, 21 is an in vivo and in vitro short-term screening method which has been widely used to detect genotoxic effects.…”
Section: Discussionmentioning
confidence: 99%